RESEARCH OF KNITTING STRUCTURE STABILITY PARAMETERS - KHOLIKOV, KURBONALI; GULYAEVA , GULFIA; ILLARION , SHIN; MUKIMOV, MIRABZAL (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The aim of research is studying the mechanism of deformation of knitwear under the application of an external load is considered as a process of violation of the internal balance of the system of loops using the triangle of possible (limiting) states of the parameters of the loops.